Photocatalytic Activity of TiO2 Nano Supported on Membrane Cellulose Acetate/Nata De Coco (CA/NDC) in Photodegradation of Methylene Blue - Roro Ernia Prawithasari; Ilma Fadilah; Mudjijono Mudjijono; Teguh Endah Saraswati; Dwidjono Hadi Darwanto (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Study of synthesis and effectiveness of membrane catalyst of cellulose acetate/nata de coco-TiO2 nano (CA/NDC-TiO2 nano) in photodegradation of methylene blue in batch system has been investigated. TiO2nanoparticles were synthesized by hydrothermal method followed by calcination at 450oC. Scanning Electron Microscopy (SEM) images indicate nano TiO2 has been successfully synthesized with average particle diameter as 88,63±4,37 nm. X-ray diffraction pattern (XRD) of nano TiO2 shows some characteristic peaks of anatase TiO2 were still existed. Membrane photocatalyst of CA/NDC- nano TiO2 was prepared via phase inversion method by mixing TiO2 nanoparticles with CA casting solution. Thermogravimetric analysis shows three decomposition steps of CA/NDC-nano membrane as well as CA/NDC membrane. Photodegradation of methylene blue was conducted with nano-TiO2 particles and CA/NDC-TiO2 membrane for 50 minutes in batch system. The absorbance changes were measured by spectrophotometer at wavelength of 664.6 nm. The result shows the photodegradation rections tended to follow second order reaction. According to the rate constant value, k, the photocatalytic effectivity using CA-NDC/nano TiO2 membrane and nano TiO2photocatalysts in metilen blue photodegradation, statistically were not significantly different.